2003
DOI: 10.1301/nr.2003.marr.107-113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Insufficiency in Canada and the United States: Importance to Health Status and Efficacy of Current Food Fortification and Dietary Supplement Use

Abstract: Several recent studies have identified a surprisingly high prevalence of vitamin D insufficiency in otherwise healthy adults living in Canada and the United States. Most striking are the effects of latitude, season, and race. Also noteworthy is that dietary vitamin D is not reaching the population in greatest need, nor is it very protective against insufficiency. Fluid milk, as the predominant vehicle for vitamin D fortification, is apparently not very effective in staving off vitamin D insufficiency in adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…In the NGHS, fortified milk and milk products were the most common food sources of vitamin D; milk provided over 42% of all vitamin D at all visits. These findings are in accord with national data [16, 34, 36, 41, 42] demonstrating the important contribution of fortified milk to vitamin D intake in adolescence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the NGHS, fortified milk and milk products were the most common food sources of vitamin D; milk provided over 42% of all vitamin D at all visits. These findings are in accord with national data [16, 34, 36, 41, 42] demonstrating the important contribution of fortified milk to vitamin D intake in adolescence.…”
Section: Discussionsupporting
confidence: 91%
“…The current and previous NGHS findings [45] add to the growing evidence that racial disparities exist in vitamin D intake [31, 34, 46]. In agreement with past studies [37, 41, 47] African American girls consumed less fortified milk compared with their white counterparts, perhaps partly attributed to lactose intolerance known to be common in this ethnic group [31, 43]. White girls more often consumed lower-fat milks whereas African-American girls more often obtained vitamin D from higher fat milks, higher fat meats and meat alternatives (sausage, ground beef, eggs), and margarine.…”
Section: Discussionsupporting
confidence: 89%
“…Combining low intake with indoor lifestyle and sun-avoiding behaviors including sunscreen use, it is not surprising that low vitamin D status is endemic. 3-6 The skeletal health consequences of vitamin D deficiency (calcium malabsorption and skeletal fragility) have long been recognized. More recently it has become appreciated that low vitamin D status leads to muscle weakness, falls and potentially a multitude of non-skeletal morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…5-7 At the same time, a number of surveys have suggested that vitamin D deficiency or insufficiency may be more common than previously believed. 8,9 Because of the implications of these observations for public health, considerable effort is now being given to examining the vitamin D exposure of various populations and to determining the levels of vitamin D that are associated with reduced cancer risk and optimal bone health.…”
Section: Introductionmentioning
confidence: 99%